Student Digital Entrepreneurship: A Systematic Literature Review using The PRISMA Framework - Septiawan, Edo (Indo-MathEdu Intellectuals Journal, 2025)
The rapid advancement of digital technology has opened new avenues for entrepreneurship, particularly among university students. As digital natives, students are increasingly engaging in entrepreneurial activities by leveraging digital platforms, tools, and infrastructures. This study aims to provide a comprehensive synthesis of existing research on student digital entrepreneurship through a Systematic Literature Review (SLR) guided by the PRISMA framework. The analysis focuses on identifying key factors, trends, and challenges faced by student entrepreneurs in digital environments. A total of 50 articles were initially gathered using Watase UAKE and screened according to inclusion and exclusion criteria. After rigorous filtering and eligibility assessment, 8 studies were included for final synthesis. Results show that digital entrepreneurship among students is driven by factors such as innovation opportunities, flexibility, and access to digital tools, but also faces barriers such as limited digital literacy, infrastructure disparities, and the need for cross-sector collaboration. The study concludes with recommendations for strengthening student entrepreneurship ecosystems and highlights areas for future research, especially in local and developing country contexts.